A high-performance CMOS-SOI antenna switch for the 2.5-5-GHz band. - Tinella, C.
Taking full advantage of the high resistivity substrate and underlying oxide of silicon-on-insulator (SOI) technology, a high-performance CMOS single-pole double-throw (SPDT) T/R switch for Bluetooth class-II applications has been designed and fabricated in a partially depleted 0.25-μm SOI process. To compare the influence on losses and isolation of the substrate resistivity, the switch has been integrated above standard and high resistivity (20 Ω·cm and 1 kΩ·cm) substrates. The switch over the standard resistivity substrate exhibits 1 dB of insertion loss and 45dB of isolation at 2.4 GHz. With the high resistivity substrate, the overall performances are strongly improved until 0.7-dB insertion loss and a 54-dB isolation at 2.4 GHz. At 5 GHz, the switch over the high resistivity substrate keeps insertion loss and isolation at 1 and 46 dB, respectively. In both cases, the measured 1-dB input compression point is 12 dBm. The targeted Bluetooth class-II specifications have been fully fitted.
Keywords: 0.25 micron; 0.7 dB; 1 dB; 1 kohmcm; 2.5 to 5 GHz; 20 ohmcm; Bluetooth class-II transceiver; CMOS-SOI antenna switch; Insertion loss; Isolation; Partially-depleted SOI technology; Single-pole double-throw T/R switch; Substrate resistivity